2019
DOI: 10.3389/fimmu.2019.02814
|View full text |Cite
|
Sign up to set email alerts
|

JAK Inhibitors and Oxidative Stress Control

Abstract: Primary Sjögren's syndrome (SjS) is a complex autoimmune epithelitis, with few treatment options, but the use of Janus kinase (JAK) inhibitors is promising because suppression of the JAK/signal transducer and activator of transcription (STAT) pathway improves sicca manifestations. Playing a primary and pathogenic role in disease development, the oxidative stress response is upregulated in activated salivary gland epithelial cells (SGECs) from patients with SjS. Therefore, the aim of this study was to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 59 publications
2
25
1
Order By: Relevance
“…35 JAK/STAT signaling pathway participates in a variety of pathological processes and regulating JAK/STAT can alleviate cell damage caused by oxidative stress. 36 Activation of JAK1/STAT1 signaling was required for increased expression of Beclin-1 , a key regulator of autophagy, 37 which is consistent with our results showing that MPH treatment significantly increased the protein expression of p-JAK1/p-STAT1 in 661 W cells.…”
Section: Discussionsupporting
confidence: 88%
“…35 JAK/STAT signaling pathway participates in a variety of pathological processes and regulating JAK/STAT can alleviate cell damage caused by oxidative stress. 36 Activation of JAK1/STAT1 signaling was required for increased expression of Beclin-1 , a key regulator of autophagy, 37 which is consistent with our results showing that MPH treatment significantly increased the protein expression of p-JAK1/p-STAT1 in 661 W cells.…”
Section: Discussionsupporting
confidence: 88%
“…The blockade of Janus kinase (JAK)/signal transducer and activator of transcription (STAT) signalling may be considered of therapeutic applicability in pSS. It is well known that the use of JAK inhibitors in pSS is promising because suppression of the JAK/STAT pathway improves sicca manifestations [ 113 , 114 ]. Pringle et al demonstrated, recently, that SG precursor cells react to pro-inflammatory cytokines by proliferation and apparent cell death, presumably by signalling through the JAK/STAT pathway, implying that inhibitors of JAK/STAT signalling may also interfere with the homeostasis of the SG epithelium [ 115 ].…”
Section: Future Perspectives On Alternative Molecular Mechanisms Mmentioning
confidence: 99%
“…The blockade of Janus chinasi (JAK)/signal transducer and activator of transcription (STAT) signalling may be considered of therapeutic applicability in pSS. It is well known that the use of JAK inhibitors in pSS is promising because suppression of the JAK/STAT pathway improves sicca manifestations [114,115]. Pringle et al demonstrated, recently, that SG precursor cells react to pro-inflammatory cytokines by proliferation and apparent cell death, presumably by signalling through the JAK/STAT pathway, implying that inhibitors of JAK/STAT signalling may also interfere with the homeostasis of the SG epithelium [116].…”
Section: Smad7 Functions As Inhibitor Of Jak/stat Pathway In Ssmentioning
confidence: 99%